2017
DOI: 10.1155/2017/2784146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Frequency Ultrasonic-Assisted Enzymolysis on the Physicochemical and Antioxidant Properties of Corn Protein Hydrolysates

Abstract: The aim of this study was to investigate the effect of low-frequency ultrasound on the enzymolysis of corn protein. A L 9 (3 4 ) orthogonal design was used to optimize ultrasound pretreatment conditions. Degree hydrolysis (DH), conversion rate of protein (CR), and DPPH IC 50 were selected as analytical indicators. Under the optimal ultrasound conditions (5 W/L power, 2 s/2 s on/off time, 50 ∘ C temperature, and 25 min time), the DH, CR, and radical (DPPH • ,• OH) scavenging capacities were significantly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 39 publications
1
37
2
Order By: Relevance
“…Thus, an improvement in the alcalase activity to facilitate the enzymolysis and then release more active‐peptides with high antioxidant capacities in suspension. Comparable observation has been indicated in previous works (Abdualrahman et al, ; Liang et al, ). Finally, sonication treatments over control were more helpful for enzymolysis of sunflower‐meal protein to prepare hydrolysates with high antioxidants activities.…”
Section: Resultssupporting
confidence: 90%
“…Thus, an improvement in the alcalase activity to facilitate the enzymolysis and then release more active‐peptides with high antioxidant capacities in suspension. Comparable observation has been indicated in previous works (Abdualrahman et al, ; Liang et al, ). Finally, sonication treatments over control were more helpful for enzymolysis of sunflower‐meal protein to prepare hydrolysates with high antioxidants activities.…”
Section: Resultssupporting
confidence: 90%
“…Degree of hydrolysis (DH) is defined as the percentage of cleaved peptide bonds compared with the total number of peptide bonds in the substrate of interest (Ravallec‐Plé, Gilmartin, Van‐Wormhoudt, & Le‐Gal, ), and in the present study, the DH was measured by the pH‐stat method according to Adler‐Nissen () and Liang et al (). The calculation formula was DH (%) = 100 × B Nb/( α Mp × htot), in which B is the volume (ml) of NaOH used; Nb is the concentration of NaOH; α is the mean dissociation degree of α‐NH2 in the protein substrate, with a value of 0.985; and htot is the total number of peptide bonds, which is a fixed value for a protein and is generally taken to have an empirical value of 8 mmol/g of protein.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of ultrasonic and heat treatment on the enzymatic hydrolysis of barley beer waste protein by Alcalase showed that the ultrasonic pretreatment (50 kHz) can increase the antioxidant activity of protein hydrolysates and promote the release of PAs [104]. Under optimal ultrasonic conditions, low-frequency ultrasound-assisted enzymatic hydrolysis can effectively improve DH and conversion rate of corn protein and the free radical scavenging activity of the hydrolysate, and promote the formation of short-chain peptides (200-3000 Da) containing hydrophobic amino acids [105]. HP pretreatment/auxiliary treatment can increase the hydrolysis rate and DH of the substrate protein, promote the release of low Mw peptides and essential amino acids, and improve the antioxidant activity of the hydrolysate [106], which has been applied to promote the proteolysis process of legume [107,108] and peanut protein [109].…”
Section: Sourcementioning
confidence: 99%